The evaluation of bioretention mesocosm for treatment of urban stromwater runoff - Lee, J.Y.; Kim, H.; Han, M. (Taylor & Francis Group, 2011)
The Bioretention system is used to uniformly minimize, detain, and retain runoff according to the hydrologic cycle, which designates reducing runoff volume, peak discharge rates and timing. Also, it is an alternative to conventional urban BMP structures. The Bioretention system can provide excellent pollutant removal and recharge for the first flush of stormwater runoff. Designed bioretention systems remove SS, metals, N, and P. specifically; vegetated bioretention mesocosm can effectively remove pollutants. For this study, 6 mesocosms were created using PVC rectangle box (500D × 500L × 800 H). Half of them were vegetated with sedum spp./grasses, while the other half had no vegetation. The mesocosms were comprised of 200 mm mixture of palletizing soils and sandy loam soils as top layer soils, 400mm loamy sand as middle layer, and 200mm pea gravel as bottom layer. The synthetic storm water and treatment plant effluent were used for all testing. The synthetic storm water was based on the average pollution loading taken from the Yeoung―dong Highway. Influent and effluent concentrations were compared on a storm by storm basis for all pollutants. Average effluent removal and retention rates of TN, TSS and TP by vegetated systems were 56%, 90%, and 58%, respectively. On the other hand, in non―vegetated system, they, were 26%, 87% and 36%. These results indicated that the bioretention system removes pollutants through the complex interactions involved among plants, fungi, microbes and media properties. ？ 2008 Taylor & Francis Group, LLC.